A Short Review of Recent Trends in Photovoltaics Research Using Van-der Waals Materials 반데르발스 재료를 사용한 태양광발전 연구의 최근 동향에 대한 간략한 검토 - Park, Hyeong Gi; Lee, Jae Hyun; Heo, Keun (Journal of Korean Institute of Metals and Materials, 2024)
In recent years, the exploration of van der Waals materials has taken center stage in the field of advanced materials research. Studies have delved deeply into the multifaceted characteristics of these materials, and in particular their potential applications in solar cell technology. Van der Waals materials, named after the unique forces binding their layers, are of high interest because of their unparalleled physical and chemical properties. Their two-dimensional (2D) nature offers a plethora of advantageous features, including a high surface-to-volume ratio, which is crucial to enhanced light absorption and electron transport. The tunable electronic properties of these materials also offer a versatile platform for customizing behavior to meet the specific requirements of solar cell applications. Their distinctive optical characteristics can also be enhanced to improve light absorption and reduce energy losses, thereby increasing overall solar cell efficiency. Recent research has not only investigated the inherent properties of van der Waals materials but also explored various techniques to combine and stack them. Such methodologies aim to exploit and optimize the synergistic effects of different materials, paving the way for next-generation solar cells with improved performance metrics. A comprehensive examination of the operating principles of these materials provides insights into their interaction with light and their subsequent electrical behavior. The study concludes with a forward-looking perspective, emphasizing how the integration of van der Waals materials could very well revolutionize the solar cell industry. Their potential to significantly boost the efficiency and stability of solar cells positions them as promising candidates for future sustainable energy solutions.
Keywords: 2d transition metal dichalcogenides; Advanced material research; Dichalcogenides; Interface engineering; Photovoltaics; Physical and chemical properties; Recent trends; Solar cell technology; Two-dimensional; Van der Waal; 2D Transition Metal Dichalcogenides; Interface Engineering; Photovoltaics; Van der Waals